Grasses of Hastinapur - Murty, Y. S.; Singh, V. (Indian Forester, 1960)
In this paper 87 species of grasses belonging to 57 genera have been enumerated. They have been collected from Hastinapur, which falls under the Upper Gangetic Plain.